2020
DOI: 10.32983/2222-4459-2020-2-187-192
|View full text |Cite
|
Sign up to set email alerts
|

The Theoretical Aspects of the Functioning and Development of Forestry in Ukraine

Abstract: The main aim of this article is to deepen the theoretical provisions of the functioning and development of forestry in Ukraine, allocating the features of economic activity in this sphere. The article puts special emphasis on the definition of the essence of the category of «forestry». To do this, the contents of such definitions as: «forest sector», «forestry», «forest complex», «forest industry», «forest-industry complex» and «forest-based industry sector» were analyzed. A detailed study of these categories,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…As stated in [12], "Forests also are central to maintaining the environmental commons. Nearly 90% of terrestrial biodiversity is found in the world's forests, with a disproportionate share in the forests of developing countries.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…As stated in [12], "Forests also are central to maintaining the environmental commons. Nearly 90% of terrestrial biodiversity is found in the world's forests, with a disproportionate share in the forests of developing countries.…”
Section: Discussionmentioning
confidence: 99%
“…Theoretical and methodological bases of forest management, issues of efficiency of its functioning, assessment, complex use and restoration of forest resources are investigated in the works [4][5][6][7][8][9][10][11][12][13][14].…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation